On the heat transfer of the anatase titanium dioxide nanocrystals. (26th June 2008) - Lakshmi, P. Vinotha Boorana; Rajkumar, N.; Ranganathan, B.; Ramachandran, K.
Titanium dioxide (TiO2) nanocrystals are synthesised by chemical route and characterised for structural and optical properties. The heat transfer in the nanoparticles is studied from the thermal properties of the nanoparticles by photoacoustic spectroscopy (PA).